Mycoplasma pneumoniae Infection Associated C3 Glomerulopathy Presenting as Severe Crescentic Glomerulonephritis. (27th September 2021) - De Silva, Lalani; Jayasinghe, Dinesha; Amarathunga, Priyani
Abstract : C3 glomerulopathy (C3GP) is a group of diseases caused by a deregulated complement system, which encompasses both dense deposit disease and C3 glomerulonephritis. Renal manifestations of C3GP are primarily of proliferative glomerulonephritis, and only a few case reports of crescentic glomerulonephritis (CGN) in association with C3GP are available. Here is a case of an adult South-Asian female, who was diagnosed as seropositive acute Mycoplasma pneumoniae infection, with associated systemic manifestations, including immune-type extravascular haemolysis and nephrotic range proteinuria. Subsequent renal biopsy revealed CGN with disrupted Bowman's capsules and necrotizing lesions. Immunofluorescence showed coarse granular mesangial C3 deposits with negative IgM, IgG, IgA, and C1q. The immunomorphological phenotype raised two possibilities including C3GP and infection-related glomerulonephritis (IRGN). Persistent proteinuria with no evidence of resolution even after 6 months of follow-up favoured C3GP over IRGN. The patient proceeded to end-stage renal failure requiring renal replacement despite aggressive immunosuppression. This case illustrates the rare association of CGN with C3GP induced by Mycoplasma pneumoniae infection, highlighting the importance of correct diagnosis as well as timely identification of triggering factors in CGN on patient outcome.